2021
DOI: 10.1186/s12889-021-11206-9
|View full text |Cite
|
Sign up to set email alerts
|

Protocol of the Cologne Corona Surveillance (CoCoS) Study– a prospective population-based cohort study

Abstract: Background Surveillance strategies are critical to cope with the current SARS-CoV-2 pandemic and to evaluate, as well as adjust government-imposed countermeasures. Incidence estimates are widely based on laboratory confirmed cases reported by health authorities. Prevalence and incidence data of SARS-CoV-2 is still scarce, along with demographic and behavioural factors associated with infection risk. Methods The Cologne Corona Surveillance Study wil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 10 publications
0
3
0
1
Order By: Relevance
“…The used invasive methods are generally safe [ 24 ], and the app-based questionnaires make it possible to answer them regularly and remotely. Compared to face-to-face or telephone interviews used in other studies [ 11 , 12 ], more interviews can be conducted due to the lower survey burden and lower costs. In addition, there is no risk of infection linked to in-person meetings.…”
Section: Discussionmentioning
confidence: 99%
“…The used invasive methods are generally safe [ 24 ], and the app-based questionnaires make it possible to answer them regularly and remotely. Compared to face-to-face or telephone interviews used in other studies [ 11 , 12 ], more interviews can be conducted due to the lower survey burden and lower costs. In addition, there is no risk of infection linked to in-person meetings.…”
Section: Discussionmentioning
confidence: 99%
“…The study reported here is cross-sectional. It represents a further development of earlier surveys conducted as part of CoCoS project [ 22 24 ]. The procedure was approved in advance by the Ethics Committee of the Medical Faculty of the University of Cologne and the Ethics Committee of the North Rhine Medical Association.…”
Section: Methodsmentioning
confidence: 99%
“…Dies ist mangels einer großen Bevölkerungskohorte die beste Annäherung an die tatsächliche Fallverteilung. Eine solche Kohortenstudie wurde in Köln durchgeführt und könnte weitere Aufschlüsse zur Inzidenz generieren [ 26 ]. Zum jetzigen Zeitpunkt lässt sich eine Verzerrung bei der Erkennung und dem Ausmaß der Untererfassung von Fällen, z.…”
Section: Diskussionunclassified